Componential Analysis Of Proverbs In Uzbek And English Languages - Saydullayeva Surayyo Serajiddinovna (Euro Asian Journal Publishing, 2025)
This article is dedicated to the component-structure analysis of phraseological units formed as proverbs in Uzbek and English. The article analyzes proverbs as components of compound and complex sentences, which are divided into components and explained through examples
Keywords: component-structure; morphological tools; syntactic analysis